Visible-Light-Mediated Synthesis of Anomeric S-Aryl Glycosides via Electron Donor–Acceptor Complex Using Thianthrenium Salts - Zhuoyi Zhou; Yufeng Zhang; Zhiqiang Yu; Yuping Liu; Zhen Wang; Qingju Zhang; Liming Wang (Molecules)
S-Aryl glycosides are not only popular glycosyl donors in carbohydrate chemistry but also serve as valuable tools in various biological studies, which has brought significant attention to their preparation. However, there remains a pressing need for greener synthesis methods in this area. In response, a mild, sustainable, and metal- and photocatalyst-free electron donor–acceptor (EDA)-mediated approach for synthesizing S-Aryl glycosides using 1-thiosugar and aryl thianthrenium salt was developed. Our strategy utilizes 1-thiosugar as the donor, overcoming the traditional reliance on electron-rich thiols, such as aryl or carbonyl thiols, typically required for forming EDA complexes.